Age‐Dependent Predictive Value of Endothelial Dysfunction for Arrhythmia Recurrence Following Pulmonary Vein Isolation. Issue 9 (9th September 2016) - Matsuzawa, Yasushi; Suleiman, Mahmoud; Guddeti, Raviteja R.; Kwon, Taek‐Geun; Monahan, Kristi H.; Lerman, Lilach O.; Friedman, Paul A.; Lerman, Amir
Abstract : Background: The mechanisms of atrial fibrillation (AF) are highly divergent. The prevalence of AF increases significantly with age, and underling mechanisms might vary with age. Endothelial dysfunction may be associated with AF and atrial arrhythmia recurrence after catheter ablation. We tested the hypothesis that the impact of endothelial dysfunction on arrhythmia recurrence following catheter ablation is age dependent. Methods and Results: This study enrolled 92 participants with AF undergoing catheter ablation. Endothelial function was assessed by peripheral arterial tonometry before ablation, and the natural logarithmic transformation of reactive hyperemia index was calculated. Endothelial dysfunction was defined as a natural logarithmic transformation of reactive hyperemia index <0.618 (median). Participants were followed for atrial tachycardia, flutter, and fibrillation recurrence for a median of 14 months. The mean age was 57±10 years. There was significant interaction between age and endothelial dysfunction in association with recurrence of AF ( P =0.029) and any atrial arrhythmia ( P =0.015), and the risk associated with endothelial dysfunction for arrhythmia recurrence was higher in younger versus older participants. Participants were divided into 2 age groups at a threshold of 60 years. Among participants aged ≤60 years, multivariate Cox proportional hazards analysis revealed the independent association between endothelial dysfunction and increased risk of arrhythmia recurrence (hazard ratio for AF 4.18 [95% CI 1.33–15.82], P =0.014, and for any atrial arrhythmia 3.62 [95% CI 1.29–11.81], P =0.014). Kaplan–Meier analysis showed that participants with endothelial dysfunction had significantly higher rates of recurrence of AF ( P =0.01) and any atrial arrhythmia ( P =0.002). Conclusions: The risk associated with endothelial dysfunction for arrhythmia recurrence following catheter ablation was age dependent and was higher in younger participants.